KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL MATEMATIKA PADA PENERAPAN MODEL PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION) - Hastari, Ratri Candra; Zuhroh, Yuyun Ekawati; Purwanto, Purwanto; Susiana, Anis (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
The purpose of this study is to describe the types of mistakes made by students in solving the problems of education statistics course on the application of direct instruction model. The results of this study are expected to be useful for: helping students to improve and reduce errors on the solution of the problem and can be used as a consideration of lecturers in providing appropriate learning steps to address the error in the solution of problems experienced by students. The research instrument used is a test question. The type of research is qualitative. Data analysis in qualitative research conducted since before, during, and after finished in the field. Based on the results of observations, tests, and interviews, shows that many students made misconceptions. Errors in applying formulas in determining quartiles, variance, standard deviation on single data or classified data. Based on the interview quote obtained data that students have difficulty in understanding the concepts in the education statistics course.